2009
DOI: 10.1007/s10549-009-0562-3
|View full text |Cite
|
Sign up to set email alerts
|

XRCC3 Thr241Met polymorphism and breast cancer risk: a meta-analysis

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. Abstract XRCC3 (X-ray repair complementing defective repair in Chinese hamster cells 3) is a member of the RecA/ Rad51-related protein family that participates in homologous recombination, maintaining chromosome stability and participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Contrary to our meta-analysis, Chen et al demonstrated that the association implicating the A2455G G allele pertained to East Asian populations and premenopausal women. Regarding the issue of race, close inspection of data revealed that during the examination of ''East Asian'' populations, Chen et al had merged a study on Indian populations [56] with other studies on Chinese and Japanese subjects; in our algorithm [12][13][14][15], Indian studies have been included in the greater subset of Caucasian (Indo-european) race, a fact which seems closer to the existing data in the field of physical anthropology [70]. Importantly, it should be declared that merging of Chinese/ Japanese and Indian studies given the larger sample of studies in the present meta-analysis still did not lead to significant results (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to our meta-analysis, Chen et al demonstrated that the association implicating the A2455G G allele pertained to East Asian populations and premenopausal women. Regarding the issue of race, close inspection of data revealed that during the examination of ''East Asian'' populations, Chen et al had merged a study on Indian populations [56] with other studies on Chinese and Japanese subjects; in our algorithm [12][13][14][15], Indian studies have been included in the greater subset of Caucasian (Indo-european) race, a fact which seems closer to the existing data in the field of physical anthropology [70]. Importantly, it should be declared that merging of Chinese/ Japanese and Indian studies given the larger sample of studies in the present meta-analysis still did not lead to significant results (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For each polymorphism, four different ORs were calculated: (i) heterozygous carriers versus ''wild type'', (ii) homozygous carriers versus ''wild type'', (iii) dominant model, i.e., heterozygous and homozygous carriers grouped together versus wild type, and (iv) recessive model, i.e., homozygous carriers versus ''wild type'' and heterozygous carriers grouped together. Separate analyses were performed in Caucasian (IndoEuropean), Chinese, and African populations, according to the algorithm adopted in our previous meta-analyses [12][13][14][15]. Separate analyses were performed on premenopausal and postmenopausal women.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…homozygous carriers versus 'wild type' and heterozygous carriers grouped together. Separate racespecific analyses were considered in case relevant data existed, according to the algorithm adopted in our previous meta-analyses [10][11][12][13][14]. In case of zero cells, an appropriate continuity correction (addition of 0.5) was implemented [10].…”
Section: Statisticsmentioning
confidence: 99%
“…Following the valuable methodological remarks by Mao et al [1] regarding our metaanalysis on glutathione-S-transferase polymorphisms and breast cancer risk [2], we decided to present elaborate sensitivity analyses on Hardy-Weinberg Equilibrium (HWE) in our three previous meta-analyses examining MDM2 SNP309 [3], CASP8 [4] and XRCC3 Thr241Met [5] polymorphisms and breast cancer risk.…”
mentioning
confidence: 99%